Changes of D dimer in women with gestational diabetes and healthy women after elective cesarean section - Fatemeh Mallah; Mina Zeinalzadeh; Dara Alvandfar (Mashhad University of Medical Sciences, 2021)
Introduction: Due to the increasing prevalence of gestational diabetes, which is one of the indications for cesarean section, and both of these cases have adverse effects on the coagulation pathway, this study was performed with aim to compare the level of D-dimer in two groups of healthy and diabetic pregnant women after cesarean section to assess the coagulation risks after cesarean section. Methods: This descriptive study was performed in 2019 on 150 healthy and gestational diabetes women who were candidates for elective cesarean section in 2019. The level of D-dimer was measured on the day before surgery, the day after surgery, on the seventh and fourteenth days for both groups. Data were analyzed by SPSS software (version 22) and Independent t-test, Chi-square, regression and Spearman correlation tests. P<0.05 was considered statistically significant. Results: The level of D-dimer on the day after surgery had the most statistically significant difference between healthy and gestational diabetes women (P=0.001). Also, on seven days after surgery (P=0.012) and 14 days after surgery (P=0.039), the amount of D-dimer was significantly higher in women with gestational diabetes than healthy women. It was also found that smoking (P=0.031) and previous history of pregnancy (P=0.041) were significantly associated with increased D-dimer levels in women with gestational diabetes. Conclusion: Gestational diabetes plays a role in increasing the level of D-dimer and can lead to an increase in plasma level of D-dimer.